The Nature of Scientific Knowledge - McCain, Kevin (Springer, 2016)
The goal of this book is to provide a comprehensive and accessible introduction to the epistemology of science. To the degree that it is successful, this book introduces readers to epistemology in general as well as the particular nuances of scientific knowledge. The chapters that follow, while far from exhaustive treatments of the various topics, provide readers with a solid introduction to philosophical topics that will be of particular use for those seeking to better understand the nature of scientific knowledge. My own understanding of the nature of scientific knowledge has greatly benefited from discussions with many colleagues and friends:Marshall Abrams, Jon Altschul, Bryan Appley, John G. Bennett, Mike Bergmann, Mike Bishop, Kenny Boyce, Brandon Carey, Eli Chudnoff, Christopher Cloos, Earl Conee, Brett Coppenger, Andy Cullison, Trent Dougherty, John Dudley, Rich Feldman, Bill Fitzpatrick, Richard Fumerton, Chris Gadsden, Jeff Glick, Alvin Goldman, David Grober- Morrow, Ali Hasan, Sommer Hodson, Kostas Kampourakis, Matt King, Court Lewis, Clayton Littlejohn, Todd Long, Jack Lyons, Peter Markie, Josh May, Matt McGrath, Andrew Moon, Alyssa Ney, Tim Perrine, Kate Phillips, Ted Poston, Jason Rogers, Bill Rowley, Carl Sachs, Greg Stoutenburg, Philip Swenson, Chris Tweedt, Jonathan Vogel, Brad Weslake, Ed Wierenga, Chase Wrenn, Sarah Wright, and several others. Thank you all. I am particularly grateful to John Dudley, Matt Frise, and Kostas Kampourakis. John and Matt both read and provided helpful comments on significant portions of this book. Kostas provided me sound advice and support at every stage of this project, and it was his encouragement that prompted me to write this book in the first place. Finally, I am deeply indebted to my fiancée, Molly Hill, for the love and support that make this project and many others possible. In places (particularly, chapters nine and ten) material from the following article is reprinted with kind permission from Springer: “Explanation and the Nature of Scientific Knowledge.” Science & Education, (2015) 24 (7–8): 827–854. I am grateful to the publishers, journal editor, and anonymous referees for helpful advice concerning this material.
An Explanatory Approach